2021
DOI: 10.1556/1647.2021.00049
|View full text |Cite
|
Sign up to set email alerts
|

Added predictive value of right ventricular ejection fraction compared with conventional echocardiographic measurements in patients who underwent diverse cardiovascular procedures

Abstract: Background and AimRight ventricular (RV) ejection fraction (EF) assessed by 3D echocardiography is a powerful measure to detect RV dysfunction. However, its prognostic value in routine clinical practice has been scarcely explored. Accordingly, we aimed at investigating whether RVEF is associated with 2-year all-cause mortality in patients who underwent diverse cardiovascular procedures and to test whether RVEF can overcome conventional echocardiographic parameters in terms of outcome prediction.Patients and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, speckle-tracking refers only to the longitudinal shortening of the RV using a single apical four-chamber cut and neglects the two other motion directions of the ventricular contraction. Thus, the use of 3D echocardiography is essential for a comprehensive assessment of RV volumes and function that goes beyond the importance of longitudinal shortening (21). Therefore, in our study, we utilized 3D evaluation of the RV, and as anticipated, patients with significant TR showed larger RV volumes.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, speckle-tracking refers only to the longitudinal shortening of the RV using a single apical four-chamber cut and neglects the two other motion directions of the ventricular contraction. Thus, the use of 3D echocardiography is essential for a comprehensive assessment of RV volumes and function that goes beyond the importance of longitudinal shortening (21). Therefore, in our study, we utilized 3D evaluation of the RV, and as anticipated, patients with significant TR showed larger RV volumes.…”
Section: Discussionmentioning
confidence: 93%
“…Four studies were prospective, while six were retrospective. Only three studies reported associations with all-cause mortality, 13,22,24 the others reported composite cardiopulmonary endpoints (Table 1). We assessed the risk of bias within the studies using the QUIPS tool (Supplementary Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In three instances (including 3-3 studies), there was an apparent overlap between the patient cohorts; 9,13-17 therefore, studies with a higher number of participants were included. 13,15,17 Overall, ten 13,15,[17][18][19][20][21][22][23][24] independent studies were included in the final quantitative analysis (Figure 1), which reported the impact of unit change of RVEF and TAPSE (n=8), 13,16,18,[20][21][22][23][24] or FAC (n=7), 13,[19][20][21][22][23][24] or FWLS (n=7), 17,[19][20][21][22][23][24] on clinical outcomes (all-cause mortality and/or cardiopulmonary adverse events) as HRs. Four studies were prospective, while six were retrospective.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…RVEF might be a universal biomarker that refines risk stratification. 10 12,14,16-23 independent studies were included in the final quantitative analysis (Figure 1), which reported the impact of unit change of RVEF and TAPSE (n = 8), 12,15,17,[19][20][21][22][23] or FAC (n = 7), 12,[18][19][20][21][22][23] or FWLS (n = 7) 16,[18][19][20][21][22][23] on clinical outcomes (allcause mortality and/or cardiopulmonary adverse events) as HRs. Four studies were prospective, while 6 were retrospective.…”
Section: Highlightsmentioning
confidence: 99%